The contribution of biological sex to heat stress-mediated outcomes in growing pigs - T.E. Rudolph; M. Roths; A.D. Freestone; R.P. Rhoads; S.H. White-Springer; L.H. Baumgard; J.T. Selsby (Animal, 2024)
Heat stress (HS) negatively impacts a variety of production parameters in growing pigs; however, the impact of biological sex on the HS response is largely unknown. To address this, 48 crossbred barrows and gilts (36.8 ± 3.7 kg BW) were individually housed and assigned to one of three constant environmental conditions: (1) thermoneutral (TN) (20.8 ± 1.6 °C; 62.0 ± 4.7% relative humidity; n = 8/sex), (2) HS (39.4 ± 0.6 °C; 33.7 ± 6.3% relative humidity) for 1 d (HS1; n = 8/sex), or (3) or for 7 d (HS7; n = 8/sex). As expected, HS increased rectal temperature (Tr) following 1 d of HS (1.0 °C; P < 0.0001) and 7 d of HS (0.9 °C; P < 0.0001). By 7 d, heat-stressed gilts were cooler than barrows (0.4 °C; P = 0.016), despite identical heating conditions. There was a main effect of sex such that barrows had higher Tr than gilts (P = 0.031). Heat-stressed pigs on d 1 had marked reductions in feed intake and BW compared to TN (P < 0.0001). One day of HS resulted in negative gain to feed (G:F) in barrows and gilts and was reduced compared to TN (P < 0.0001). Notably, following 1 d of HS, the variability of G:F was greater in gilts than in barrows. Between 1 and 7 d of HS, G:F improved in barrows and gilts and were similar to TN pigs, even though HS barrows had higher Tr than gilts over this period. Heat stress for 1 and 7 d reduced empty gastrointestinal tract weight compared to TN (P < 0.0001). Interestingly, HS7 gilts had decreased gastrointestinal tract weight compared to HS1 gilts (2.43 vs 2.72 kg; P = 0.03), whereas it was similar between HS1 and HS7 barrows. Lastly, a greater proportion of gastrointestinal contents was in the stomach of HS1 pigs compared to TN and HS7 (P < 0.05), which is suggestive of decreased gastric emptying. Overall, HS barrows maintained an elevated Tr compared to HS gilts through the duration of the experiment but also maintained similar growth and production metrics compared to gilts, despite this higher temperature.